Determination of composition based on thermal conductivity by thermistor direct heating method - Matvienko, Sergey; Shevchenko, Vadim; Tereshchenko, Mykola; Kravchenko, Anatolii; Ivanenko, Ruslan (Eastern-European Journal of Enterprise Technologies, 2020)
Thermophysical properties of various substances and mixtures were studied by the non-destructive method. It is proposed to determine the thermal conductivity of substances and mixtures by the thermistor direct heating method. The device was created for measuring the thermal conductivity of various substances and mixtures, the operation of which is based on measuring the temperature of thermistor heating in the test substance. The nonlinear nature of the obtained thermistor heating dependence is taken into account. Based on the studies, the possibility of determining the composition of the mixture by its thermal conductivity coefficient is shown. The results of experimental studies with reference liquids, solutions of sugar, glycerin and alcohol in water are presented. The results of the studies to determine the thermophysical properties (TPP) of biological substances (human blood and blood plasma, egg white and yolk and others), some vegetables using the method of thermistor direct heating in the temperature range from +25 °С to +40 °С are given. It is substantiated that when studying the TPP of substances by thermistor direct heating, it is possible to determine the composition of mixtures by their thermal conductivity, but it is necessary to take into account individual properties of the studied liquids. Recommendations are given for studying the TPP of substances and determining the composition of mixtures by their thermal conductivity, taking into account individual properties of the studied substances. Using the proposed method of thermistor direct heating to determine a mixture of solutions, biological materials and food products allows analyzing the composition of nanosubstances, obtaining reliable data on the degree of allergic reaction, and in determining the composition of food products – taking into account the data obtained when developing refrigeration equipment and extending the shelf life of products while maintaining their useful qualities.